A prospective study of inflammatory biomarkers in neonatal sepsis at a tertiary level hospital - Paimode, Sandeep D.; Sharma, Kuldeep Kumar; Kour, Navjot (International Journal of Contemporary Pediatrics, 2020)
Background: Sepsis in neonates is a syndrome which is characterized clinically by systemic symptoms or signs of infection and associated with bacteremia in the first 28 days of life. More than 40% of under-five deaths globally occur in the neonatal period, resulting in 3.1 million newborn deaths each year. Procalcitonin (PCT) is an early diagnostic tool for neonatal sepsis. Methods: Present prospective cross- sectional observational study was conducted at NICU of Base hospital, Delhi Cantonment from 1st Dec 2016 to Jan 31st, 2018. Universal sampling technique was followed. SPSS version 21 was used for statistical analysis. A p-value of less than 0.05 was taken as significant. Results: Out of the total 440 cases, 63% were males while rest 37% were females. Mean gestation age and birth weight of the babies was 35.6 weeks and 2.13 Kg respectively. Raised/ decreased Total Leucocyte Count (TLC) and raised pro calcitonin levels were seen in 23% and 19.8% cases respectively. Conclusions: These results indicated that the sensitivity of procalcitonin was higher than TLC for the diagnosis of culture proven neonatal sepsis. Hence, PCT is a more sensitive and useful biomarker for the diagnosis of neonatal sepsis.